Day-Case Opening Wedge High Tibial Osteotomy With Intraosseous PEEK Implant - Martin Polacek, M.D., Ph.D; Cecilie P. Nyegaard, M.D; Fredrik Høien, M.D (Elsevier, 2020)
Purpose: To evaluate the short-term clinical outcomes, complications, hospitalization time, and readmission rate related to day-case opening wedge high tibial osteotomy (OWHTO) with intraosseous PEEK (polyether ether ketone) implant, in the treatment of knee osteoarthritis. Methods: An observational study on patients treated with OWHTO using intraosseous PEEK implant was performed with a period of 12 months follow-up. Grade of Knee Injury and Osteoarthritis Outcome Score (KOOS) was assessed preoperatively, at 6 months, and at 12 months postoperatively. A simple t test was used to analyze the outcomes. P values <.05 were considered significant. Complications and revision surgeries were registered. Results: In the period from 2016 to 2017, a consecutive group of 40 patients (13 female, 27 male) with symptomatic medial knee osteoarthritis and varus malalignment were included in the study. The average age of the patients was 54.9 (± 7.6) years. In total, 30 (77%) patients met the criterion for minimal clinically important difference in KOOS scores. The KOOS symptoms improved from 58.1 ± 20 to 78.5 ± 16.5 (P < .0001), pain from 48.1 ± 18.2 to 78.6 ± 18.5 (P < .0001), activities of daily living from 59.0 ± 19.5 to 84.1 ± 15.2 (P < .0001), sport from 23.2 ± 17.6 to 55.6 ± 26.3 (P < .0001), and quality of life from 28.4 ± 12.8 to 61.5 ± 22.5 (P < .0001) at 1-year follow-up. The average hospitalization time at the Day Surgery Unit was 5.6 ± 0.7 hours, and 4 (10%) patients had to be readmitted to the hospital within 2 weeks postoperatively. The overall complication rate was 18%. Complications that required revision surgery were registered in 4 patients (10%), including 2 non-unions and 2 progressions of osteoarthritis. Conclusions: The day-case OWHTO with intraosseous PEEK implant was a success in 77% of the cases. The results and complications were comparable with other published studies. Despite a short hospitalization time, the readmission rate was low. Level of Evidence: IV, therapeutic case series.